2020
DOI: 10.48550/arxiv.2003.04912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flip-sort and combinatorial aspects of pop-stack sorting

Andrei Asinowski,
Cyril Banderier,
Benjamin Hackl

Abstract: Flip-sort is a natural sorting procedure which raises fascinating combinatorial questions. It finds its roots in the seminal work of Knuth on stack-based sorting algorithms and leads to many links with permutation patterns. We present several structural, enumerative, and algorithmic results on permutations that need few (resp. many) iterations of this procedure to be sorted. In particular, we give the shape of the permutations after one iteration, and characterize several families of permutations related to th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The segment σ 3,6 (right) is the smallest segment contained in σ that includes all of the blocks in X 3,6 (σ). The violating pairs of T are (3,6) (because of the second row) and (5,6) (because of the first row). Since (3,6) is a violating pair of T , the segment σ 3,6 is forbidden.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…The segment σ 3,6 (right) is the smallest segment contained in σ that includes all of the blocks in X 3,6 (σ). The violating pairs of T are (3,6) (because of the second row) and (5,6) (because of the first row). Since (3,6) is a violating pair of T , the segment σ 3,6 is forbidden.…”
Section: 2mentioning
confidence: 99%
“…The authors of [5] suggested considering the average size of the forward orbit of a permutation in S n under the pop-stack-sorting map. In [25], the current author conjectured that this average number of iterations is asymptotically equal to n, which is the maximum possible size of a forward orbit by Ungar's theorem.…”
Section: Further Directionsmentioning
confidence: 99%
“…We deduce that v can be written as shift β (ι(u)), where u = y 1 ⊕ • • • ⊕ y r ∈ S n and each y i is in Υ * κ i . Furthermore, there is a unique choice of β such that 0 ≤ β ≤ κ 1 − 1. hook H 1 has endpoints (−2, 0) and (2,3). The hook H 2 has endpoints (2, 3) and (4,6).…”
Section: Coxeter Stack-sorting In Type Amentioning
confidence: 99%
“…The second motivation for our terminology comes from the fact that when ≡ des is the descent congruence on W = S n , the map S ≡ des is the pop-stacksorting map. This function, which is a deterministic analogue of a pop-stack-sorting machine introduced by Avis and Newborn in [5], first appeared in a paper of Ungar's about directions determined by points in the plane [61]; it has received a great deal of attention over the past few years [1,3,4,18,19,26,32,47].…”
mentioning
confidence: 99%
“…This implies that b j (µ) = 0 < r 0 for all 1 ≤ j ≤ f 0 . We also have b j (µ) ≤ r 0 for all 3,4); one can check that µ # is indeed a 2-Pop-sortable element of Tam(ν # ). Then (r 0 , .…”
mentioning
confidence: 93%